2015
DOI: 10.1021/om500792k
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Role of 3-Iminophosphine Ligands in Palladium-Catalyzed Intermolecular Hydroamination

Abstract: This study of the electronic characteristics of (3-iminophosphine)allylpalladium triflate complexes has yielded catalysts with moderate to high activity for the hydroamination of monosubstituted allenes utilizing a wide range of amines. Herein, a new series of these catalysts was synthesized by varying the group on the imine moiety in order to explore the effect of the electronics of the ligand's imine on the catalytic activity for intermolecular hydroamination reactions. Four amine substrates were examined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Both features impact the overall efficiency and operable mechanism in known systems. In our recent work involving the mechanistic study of palladium‐catalyzed allene hydroamination, we showed that electronic effects in the supporting 3‐iminophosphine (3IP) ligands often dictate the rate‐limiting step in the mechanism for this process . With this understanding of ligand effects, we felt well‐poised to address the challenging reactivity of nickel analogues based on our previously reported palladium catalysts, especially when applied to allene hydroamination catalysis.…”
Section: Cationic [(3ip)ni(allyl)]+ Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Both features impact the overall efficiency and operable mechanism in known systems. In our recent work involving the mechanistic study of palladium‐catalyzed allene hydroamination, we showed that electronic effects in the supporting 3‐iminophosphine (3IP) ligands often dictate the rate‐limiting step in the mechanism for this process . With this understanding of ligand effects, we felt well‐poised to address the challenging reactivity of nickel analogues based on our previously reported palladium catalysts, especially when applied to allene hydroamination catalysis.…”
Section: Cationic [(3ip)ni(allyl)]+ Complexesmentioning
confidence: 99%
“…The putative nickel hydride concurrently formed in this reaction is unstable, decomposing in the absence of allene substrate and eluding adequate characterization in our hands. We previously observed a similar catalyst activation/first turnover product in palladium analogues of these nickel complexes, leading to their activity for allene hydroamination . Thus, we set out to examine the catalytic activity of these newly synthesized nickel complexes in the hydroamination of mono‐substituted allenes.…”
Section: Cationic [(3ip)ni(allyl)]+ Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions proceed by a 5‐ exo ‐allylic hydroamination process in which, once again, a π‐allyl–Pd II complex intermediate is involved in the crucial step. [4g], [4h]…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the use of allenes as substrates in such reactions allows one of the allene double bonds to be preserved for further transformations. The limited number of synthetic applications of Pd‐catalysed hydroamination reactions involving allenes reported in literature, the positive results previously reported by our research group on the transition‐metal‐catalysed reactions of allenamides and our ongoing interest in amination processes prompted us to increase the range of heterocycles available for the synthesis of biologically active compounds. Considering the allene derivatives arising from commercially available o ‐aminophenols and o ‐phenylenediamines as useful substrates, we proposed to synthesize vinyl‐substituted benzoxazoles and ‐imidazoles, two scaffolds endowed with various biological activities, for example, a recently synthesized substrate shows potential for the treatment of Alzheimer's disease .…”
Section: Introductionmentioning
confidence: 99%